The impact of the values of top managers upon their Subordinates values - Tuulik, Krista; Alas, Ruth (Journal of Business Economics and Management, 2003)
Psychologists, sociologists, economists, management scholars, as well as other researchers from other disciplines have been attempting to find answers to two fundamental questions how to get better result out from people so that these people themselves would appreciate the methods used to manage/lead them and would be happy to act in their owners, managers/leaders favour. One key factor, which has been talked about, is values and especially shared values. If the employees and their managers have common/shared values the working together would be at least emotionally easier.First Published Online: 14 Oct 2010